2018
DOI: 10.1002/jlb.3ma0317-101rrr
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dihydromyricetin on LPS-induced acute lung injury

Abstract: Dihydromyricetin (DHM), a bioactive flavonoid component isolated from Ampelopsis grossedentata, is known to have anti-inflammatory effect, but the effect of DHM on acute lung injury (ALI) is largely unknown. Here, we investigated the effect of DHM on ALI and the underlying mechanism by bioinformatic analyses and animal experiments. We found that pretreatment with DHM ameliorated lung pathological changes and suppressed the inflammation response in lung tissues after LPS challenge. The potential targets of DHM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It was reported that DHM ameliorated lung pathological changes and lung edema in ALI mice challenged by LPS or CLP, which was associated with its inhibition of secretion of inflammatory cytokines TNF-α, IL1-β, IL-6 and IL-18. The responsible mechanism involved DHM activating PPAR-α expression as well as blocking the MAPK signaling pathway [ 167 ] and NLRP3 inflammasome [ 168 ]. Moreover, DHM had similar effects to 5 mg/kg DEX.…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that DHM ameliorated lung pathological changes and lung edema in ALI mice challenged by LPS or CLP, which was associated with its inhibition of secretion of inflammatory cytokines TNF-α, IL1-β, IL-6 and IL-18. The responsible mechanism involved DHM activating PPAR-α expression as well as blocking the MAPK signaling pathway [ 167 ] and NLRP3 inflammasome [ 168 ]. Moreover, DHM had similar effects to 5 mg/kg DEX.…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…Moreover, DHM had similar effects to 5 mg/kg DEX. However, DEX inhibited Smad4 expression but DHM had no effect [ 167 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…Furthermore, DHM reduced inflammatory response via the JNK pathway in acute liver injury mice ( Wang et al, 2018a ). DHM reversed the metabolic syndrome by upregulating insulin receptor substrate-1 (IRS-1) (y612) tyrosine phosphorylation and improving insulin resistance in obese mice ( He et al, 2019 ).…”
Section: Other Mechanisms Of Dhm Except For Anti-inflammatorymentioning
confidence: 99%
“…Mediators of Inflammation Mediators of Inflammation factor NF-κB, and prostaglandin-E2 that regulate the inflammatory responses. Numerous studies reported that DHM showed anti-inflammatory activity through different molecular mechanisms such as suppression of proinflammatory cytokines (IL-1β, IL-6, IL-8, and TNF-α), activation of the production of an anti-inflammatory cytokine (IL-10), inhibition of MAPKs, suppression of the production of prostaglandins and nitric oxide, and inhibition of the transcription factor NF-κB [3,4,79,80]. The inflammatory response of the brain or the spinal cord is known as neuroinflammation, and it has an important role in the development of depression by producing cytokines, chemokines, and ROS [26].…”
mentioning
confidence: 99%